President Trump and the news media moral foundations, framing, and the nature of press bias in America - Kuypers, Jim A. (Lexington studies in political communication., 2020)
In President Trump and the News Media Kuypers analyzes policy addresses by President Trump, comparing them with reporting through lenses of framing analysis and Moral Foundations Theory. Differences point to widespread journalistic bias. The effect of this bias on reportorial practices and the functioning of the American Republic is addressed.